THU0249 C - reactive protein (CRP) is associated with high disease activity in SSC and ILD. Results from the canadian scleroderma research group (CSRG). (23rd January 2014) - Muangchan, C.; Harding, S.; Khimdas, S.; Bonner, A.; Baron, M.; Pope, J.E.
Abstract : Background: Elevated ESR in SSc is associated with morbidity yet little is known about the predictive value of C-reactive protein (CRP) in SSc. Objectives: This study was done to determine the associations of CRP in SSc subsets (overall, early, late, dcSSc, lcSSc) and organ associations with CRP. Methods: The CSRG is a large multi-site dataset comprised of patients with SSc where patient and physician reported measures and lab tests are performed annually. The frequency of elevated CRP and ESR and their relationships to clinical parameters, Scleroderma Disease Activity Score (SDAS), Scleroderma Disease Severity Score (SDSS), Health Assessment Questionnaire (HAQ) and changes between annual follow up were studied. Statistical comparisons were made for CRP in early (≤3 years from 1st non-RP symptom) vs. late SSc, diffuse cutaneous SSc (dcSSc) vs. limited cutaneous (lcSSc). CRP >8mg/L was the cut off for elevated as it was the value for 95th percentile for age and gender matched population norms. Results: 1, 043 patients aged 55.4±12.1 years, female predominant (86.1%), and disease duration of 11.0±9.5 years were analyzed of whom 38% had dcSSc, 62% had lcSSc and 10.6% were early dcSSc. Elevation of CRP occurred in 25.7% and ESR 38.2%. Baseline CRP in dcSSc (11.98±25.41 mg/L) was higher than in lcSSc (8.15±16.09 mg/L); p=0.016. SSc with disease duration ≤3 years had higher CRP (12.89±28.13 mg/L) than that with disease duration >3 years (8.60±17.06 mg/L); p=0.041. Though not be consistent in all subsets, CRP was significantly associated in overall group at p<0.01 for: ESR, MRSS, TLC<80%, FVC<80%, DLCO<75%, disease activity (SDAS), damage (SDSS), and HAQ. In early dcSSc, the frequency of elevated CRP and ESR was 41.5% and 44.2% respectively. CRP seemed to normalize in many SSc patients over time. Adding or withdrawing prednisone did not significantly change CRP but was underpowered. Conclusions: CRP is elevated in approximately one quarter of SSc patients, especially early disease. It is correlated with disease activity, severity and poor pulmonary function. Disclosure of Interest: C. Muangchan: None Declared, S. Harding: None Declared, S. Khimdas: None Declared, A. Bonner: None Declared, M. Baron: None Declared, J. Pope Grant/Research support from: Support for the CSRG is from CIHR, Scleroderma Society of Canada, Scleroderma Society of Ontario